Introduction to Engineering Design : Modelling, synthesis and problem solving strategies - Samuel, Andrew E.; Weir, John. (Oxford : Butterworth-Heinemann, 1999)
Introduction to Engineering Design covers the basic elements of engineering design for structural integrity. An essential aspect of the design process - the concept of failure, and its avoidance - is examined in detail.
Includes bibliographical references (p. 365-372) and index.
Keywords: Engineering design; Technology